Restoring a butterfly hot spot by large ungulates refaunation: the case of the Milovice military training range, Czech Republic - Konvička, Martin; Ričl, David; Vodičková, Veronika; Beneš, Jiří; Jirků, Miloslav (BMC ecology and evolution, 2021)
BACKGROUND: Refaunation/rewilding by large ungulates represents a cost-efficient approach to managing natural biotopes and may be particularly useful for areas whose biodiversity depends on disturbance dynamics and is imperilled by successional changes. To study impacts of refaunation on invertebrates, we focused on butterflies inhabiting the former military training range Milovice, Czech Republic, refaunated since 2015 by a combination of Exmoor pony ("wild" horse), Tauros cattle ("aurochs"), and European wisent. METHODS: We analysed butterfly presence-absence patterns immediately after the military use termination (early 1990s), prior to the refaunation (2009), and after it (2016-19); and current abundance data gained by monitoring butterflies at refaunated and neglected plots. We used correspondence analysis for the presence-absence comparison and canonical correspondence analysis for the current monitoring, and related results of both ordination methods to the life history and climatic traits, and conservation-related attributes, of recorded butterflies. RESULTS: Following the termination of military use, several poorly mobile species inclining towards oceanic climates were lost. Newly gained are mobile species preferring warmer continental conditions. The refaunated plots hosted higher butterfly species richness and abundances. Larger-bodied butterflies developing on coarse grasses and shrubs inclined towards neglected plots, whereas refaunated plots supported smaller species developing on small forbs. CONCLUSION: The changes in species composition following the cessation of military use were attributable to successional change, coupled with changes in species pool operating at larger scales. By blocking succession, large ungulates support butterflies depending on competitively poor plants. Restoring large ungulates populations represents a great hope for conserving specialised insects, provided that settings of the projects, and locally adapted ungulate densities, do not deplete resources for species with often contrasting requirements.
Keywords: Plants; Equus caballus; Bos taurus; Humans; Temperate grassland; Trophic rewilding; ozbrojené síly; Horses; Butterflies; lidé; Bison bonasus; koně; zvířata; Life history traits; Lepidoptera conservation; Military Personnel; Cattle; biodiverzita; Czech Republic; skot; Climatic niche traits; Animals; motýli; Česká republika; rostliny; Biodiversity